ANALISIS PENGARUH GAYA KEPEMIMPINAN, PEMANFAATAN DAN PENERAPAN TEKNOLOGI INFORMASI SIMDA KEUANGAN TERHADAP KINERJA KARYAWAN DI BPKAD KABUPATEN BLITAR - Diana Puspitasari (REVITALISASI : Jurnal Ilmu Manajemen, 2020)
This study aimed to determine the impact of leadership style, benefit and applied information technology of simda finance aplictaion simultaneous and partial on employee performance in BPKAD Blitar District. This research is explanatory research, multiple linear regression data analysis techniques. The results of the study is leadership style, use and application of simda finance aplication information technology simultaneously influence the performance of employees in the Regional Financial and Asset Management Agency (BPKAD) of Blitar District. Theoleadership ostyle to performance of employees at othe Regional Financial and Asset Management Agency (BPKAD) Blitar District. The use of Simda Finance oinformation technology has an impact to the performance of employees at the Blitar District Financial oand Asset Management Agency (BPKAD). The applied of simda finance aplictaion information technology has an impact to the performance of employees at the Blitar District Financial and Asset Management Agency (BPKAD).